A perspective on the governance of London's subsurface. Issue 1 (March 2021) - Von Der Tann, L; Metje, N; Collins, B; Melo Zurita, M
Abstract: The role of the urban subsurface for cities has long been disregarded but is recently getting more attention. To capture it, the city's geographical and geological setup, its history and the social context it is located within are of particular relevance. As a case study, this paper illustrates the context and governance of London's subsurface through the lens of a 'governance arrangement' looking at these three elements. It is highlighted that feedback loops between the material reality and the societal context – human influences on the subsurface environment – are not sufficiently recognised. The paper demonstrates how the discretionary nature of the UK's planning system puts local planning authorities on the one hand, and engineers and technical knowledge on the other hand, in central positions to mediate strategic plans and influence specific project applications and decisions. From the empirical analysis presented here, no sense of urgency is assigned to the concept of underground space planning in London at this moment in time. However, the analysis suggests a need for better understanding of the spatial and material effects of specific interventions, as well as of the according policies and strategies. Current discourses around underground data sharing or geothermal energy provision could facilitate the process towards a spatial integration of the various strategies that are in place.